Hydrogen oxidation on oxygen-rich IrO2(110). (2nd October 2018) - Li, Tao; Kim, Minkyu; Liang, Zhu; Asthagiri, Aravind; Weaver, Jason F.
ABSTRACT: We investigated the adsorption and oxidation of H2 on O-rich IrO2 (110) using temperature programmed reaction spectroscopy (TPRS) and density functional theory (DFT) calculations. Our results show that H2 dissociation occurs efficiently on O-rich IrO2 (110) at low temperature and initiates from an adsorbed H2 σ-complex on the coordinatively-unsaturated Ir atoms (Ircus ). We find that on-top oxygen atoms (Oot ), adsorbed on the Ircus sites, promote the desorption-limited evolution of H2 O during subsequent oxidation of the adsorbed hydrogen on IrO2 (110) while suppressing reaction-limited production of H2 O via the recombination of bridging HO groups (HObr ) ( 500 to 750 K) during TPRS. The desorption-limited TPRS peak of H2 O shifts from 490 to 550 K with increasing Oot coverage, demonstrating that Oot atoms stabilize adsorbed OH and H2 O species. DFT predicts that molecularly-adsorbed H2 dissociates on O-rich IrO2 (110) at low temperature and that the resulting H-atoms redistribute to produce a mixture of HObr and HOot groups, with equilibrium favouring HOot groups. Our calculations further predict that subsequent H2 O evolution occurs through the recombination of HObr /HOot and HOot /HOot pairs, and that these reactions represent desorption-limited pathways because the dissociative chemisorption of H2 O is favoured over molecular adsorption on IrO2 (110). The higher stability of HOot groups and their preferred formation causes the higher-barrier HOot /HOot recombination reaction to become the dominant pathway for H2 O formation with increasing Oot coverage, consistent with the experimentally-observed upshift in the H2 O TPRS peak temperature. Graphical abstract: